Establishment of effective plantlets regeneration protocol via isolated microspore culture in Malaysian indica rice MR219 - Abd Rahman, Zuraida; Ahmad Seman, Zulkifli; Othman, Ayu Nazreena; Ab Ghaffar, Mohamad Bahagia; Ab Razak, Shahril; Mohd Yusof, Muhammad Fairuz; Nasir, Khairun Hisam; Ahmad, Khairulmazmi; Yeow, Lit Chow; Teo, Chee How; Md Saad, Norsharina; Subramaniam, Sreeramanan (Springer, 2022)
The current study recognised the issues encountered in regenerating Malaysia MR219 rice plantlet via microspore culture and attempted to develop an efficient protocol in overcoming the restraints. In the present study, a high proportion of uninucleate microspores (49.17%) was isolated from Stage 2-Segment II panicle (59–61 days), which also exhibited the highest callus initiation rate of 8.50%. Maintenance of the panicles under a cool temperature of 4 °C for 7 days before isolating the microspores, resulted in the highest microspore viability of 58.33% and callus initiation rate of 9.33%. The microspore isolation protocol was also optimised in the present study. The filtration sieve engagement with a pore size of 80 µm and further suspension centrifugation at 800 rpm for 5 min produced the highest microspore viability percentage and callus initiation rate. The incorporation of 3.0 mg/L kinetin in conjunction with 0.5 mg/L 2,4-D greatly enhanced the callus initiation rate, with 11.33%. The callus proliferation capacity, with the formation of 481.67 mg callus, was significantly promoted by the addition of 1.0 mg/L kinetin and 0.5 mg/L 2,4-D into the growth medium. Moreover, a higher green plantlet regeneration frequency of 2.83% was induced by the supplementation of 8% sucrose, which produced an average of 3.50 green plantlets.